Treatment of Ipsilateral Femoral Neck and Shaft Fractures With Cannulated Screws and Antegrade Reconstruction Nail. Issue 5 (May 2020) - Spitler, Clay A.; Kiner, Dirk; Swafford, Rachel; Bruce, Jeremy; Nowotarski, Peter
Abstract : Summary: Ipsilateral femoral neck and shaft fractures are challenging injuries, and there are different fixation options but no consensus on a superior construct. Our preferred method is cannulated screw fixation of the femoral neck and antegrade reconstruction nailing of the shaft. Compressive fixation of the femoral neck fracture with cancellous lag screws followed by reconstruction nail placement provides compressive fixation and fixed angle support of the neck fracture while allowing for more optimal treatment of femoral shaft fractures at or above the isthmus. The purpose of this submission is to describe the surgical decision-making, surgical technique, and all surgically related complications of this technique. Abstract : Supplemental Digital Content is Available in the Text.